2004
DOI: 10.1111/j.0002-9092.2004.00653.x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of Acreage Effects of Participation in the Federal Crop Insurance Program

Abstract: The extent to which crop insurance programs have resulted in additional land being brought into production has been a topic of considerable debate. We consider multiequation structural models of acreage response, insurance participation, CRP enrollment, and input usage. Our analysis focuses on corn and soybean production in the Corn Belt and wheat and barley production in the Upper Great Plains. Our results confirm that increased participation in insurance programs provokes statistically significant acreage re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
136
2
7

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 214 publications
(161 citation statements)
references
References 11 publications
(3 reference statements)
7
136
2
7
Order By: Relevance
“…56 Because individuals generally fail to take such low-frequency, high-severity events into 51 Skees (2001);Wu (1999). 52 Goodwin et al (2004);Skees (2001). 53 Buzby et al (1994).…”
Section: Catastrophic Risk Layermentioning
confidence: 99%
“…56 Because individuals generally fail to take such low-frequency, high-severity events into 51 Skees (2001);Wu (1999). 52 Goodwin et al (2004);Skees (2001). 53 Buzby et al (1994).…”
Section: Catastrophic Risk Layermentioning
confidence: 99%
“…More detailed analyses of demand for crop insurance, i.e. the factors which really affect the purchase of insurance and future demand forecasts are usually focused on other markets, mainly in the US [Coble et al 1996;Goodwin, Vandeveer, Deal 2004;Mishra, Goodwin 2003;Sherrick et al 2004;Garrido, Zilberman 2008;Ogurtsov, Van Asseldonk, Huirne 2009].…”
Section: Risks In the Farms In Poland And Their Financing -Research Fmentioning
confidence: 99%
“…Several studies have found that insurance has a small, positive impact on production (Young, Vandeveer, and Schnepf, 2001;Goodwin, Vandeveer and Deal, 2004;Lubowski, et al, 2006). To illustrate the estimated production impacts, Lubowski, et al found that cultivated cropland in the 48 contiguous US states increased by 0.8 percent in 1997.…”
Section: Production and The Environmental Impacts Of Subsidized Crop mentioning
confidence: 99%